Sport-related injuries in Iranian basketball players: evidence from a retrospective epidemiologic study (2019-20) - Abdollahi, S.; Sheikhhoseini, R. (The Physician and Sportsmedicine, 2022)
Objectives Basketball is a contact sport with complex movements that include jumps, turns, and changes in direction, which cause frequent musculoskeletal injuries in all regions of the body. Also, injury patterns among athletes, particularly basketball players, continue to evolve and change. The current retrospective epidemiologic study aimed to investigate the incidence, severity, and sports-related risk factors of injuries in Iranian basketball players from 2019 to 2020.